2005
DOI: 10.1149/1.2008980
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Growth of Self-Organized TiO[sub 2] Nanotubes Anodically Formed in NH[sub 4]F∕(NH[sub 4])[sub 2]SO[sub 4] Electrolytes

Abstract: The anodic formation of self-organized porous TiO 2 on titanium was investigated in 1 M ͑NH 4 ͒ 2 SO 4 electrolytes containing 0.5 wt % NH 4 F by potential sweeps to 20 V SCE . By a combination of electrochemical, morphological, and compositional information we show that the sweep rate has a significant influence on the initiation and growth of the porous structures. In the first phase of the anodization process, a precursor barrier type of oxide film is formed; underneath this film pores then start growing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
209
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(224 citation statements)
references
References 48 publications
13
209
0
2
Order By: Relevance
“…In Figure 5, the value of j from the lowest to the highest are on the CG30-4000, CG30-800 and CG30-14000 samples, respectively, therefore their δ b after Stage I will decrease in that order. The value of t c at the top of TNT layers after the anodization process, also supports this relation (Figure 9), because this capping oxide layer seen at this stage is the penetrated compact oxide layer formed in Stage I [24], therefore the value of t c shows the value of δ b when TNTs started nucleation.…”
Section: The Influence Of Mechanical Preparation On the Morphologies supporting
confidence: 69%
See 1 more Smart Citation
“…In Figure 5, the value of j from the lowest to the highest are on the CG30-4000, CG30-800 and CG30-14000 samples, respectively, therefore their δ b after Stage I will decrease in that order. The value of t c at the top of TNT layers after the anodization process, also supports this relation (Figure 9), because this capping oxide layer seen at this stage is the penetrated compact oxide layer formed in Stage I [24], therefore the value of t c shows the value of δ b when TNTs started nucleation.…”
Section: The Influence Of Mechanical Preparation On the Morphologies supporting
confidence: 69%
“…electrochemical parameters such as potential [18], electrolyte types [19][20][21][22], water content [23] and sweep rates [24]. However, the influence of intrinsic factors, such as surface roughness, surface conditions and grain size and orientation of the titanium substrate are rarely studied [25][26][27][28] and the significant influence of sample preparation methods on TNT growth makes it difficult to study the effects of grain size separately [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…These layers have a limited thickness about 500-600 nm. By taking into account the importance of the pH gradient within the tube 7 , and using buffered neutral electrolytes that containing NaF or NH4F instead of HF, the thickness of the self-organized nanotube titanium oxide layers will increase more than 2 micrometer [61][62][63][64] . The third generation of the nanotubes were grown in (almost) water free electrolytes.…”
Section: Importance Of Titanium Oxide Nanostructurementioning
confidence: 99%
“…Recently, we have shown that the tubes can be grown to a length of several micrometers, giving an aspect ratio of a few hundreds. [15][16][17][18][19] This can be achieved by tailored anodization in neutral solutions containing NH 4 F 15-17 or NaF 18 or in glycerol/NH 4 F mixtures. 19 We have already used the nanotubular structures to dye-sensitize them in the visible light 4 or as a catalyst support for methanol electrochemical oxidation, 20 and we have shown how to use ion implantation 21,22 and thermal treatment to N-dope the tubes.…”
mentioning
confidence: 99%